Compositional, structural design and nutritional aspects of texture-modified foods for the elderly. (January 2022) - Gallego, Marta; Barat, José Manuel; Grau, Raúl; Talens, Pau
Abstract: Background: Texture-modified foods (TMF) are commonly used as a therapeutic strategy for people with chewing or swallowing difficulties such as the elderly, which is the fastest growing segment of the global population. These foods need to be soft, safe and easily swallowed as well as have nutritive properties and attractive sensory attributes in order to help overcome physiological dysfunctions and cover specific nutritional requirements. Scope and approach: This review provides an overview about common and novel ingredients and techniques used to obtain TMF with desired textural characteristics as well as methods or processes aimed to improve nutritional and sensory characteristics. Digestibility aspects of TMF are also presented, specially the influence of food matrix structure and material properties on digestion and bioaccessibility of nutrients. Key findings and conclusions: The design of products with textural, nutritional, and sensory characteristics suitable for the elderly should consider not only compositional and structural aspects during formulation but also the modification of food structure during oral processing and gastrointestinal digestion. Increasing the knowledge in these issues will assist the development of products with enhanced functionalities in order to meet the needs of specific populations such as the elderly. Graphical abstract: Image 1 Highlights: Design of texture-modified foods (TMF) for an ageing society. Common and novel ingredients and techniques used to obtain TMF are reviewed. Importance of compositional and structural aspects during food formulation. Modification of food structure during oral processing and digestion. Influence of food matrix structure on digestibility and nutrients bioaccessibility.